PERLINDUNGAN HUKUM DALAM PENGELOLAAN LINGKUNGAN HIDUP TERHADAP PEMBANGUNAN BERKELANJUTAN: Fadlan Kalma - Kalma, Fadlan (Qawwam : The Leader's Writing, 2022)
There are still many environmental cases that occur today, of course it can be a criticism for the Government as the organ that is fully responsible for fulfilling these rights. Various environmental problems that occur, both damage and pollution are not directly proportional to the law enforcement mechanisms implemented by the Government. Birth of Law No. 32/2009 (UU PPLH) apparently also has not been able to answer all the problems of enforcing environmental law in Indonesia. therefore in this paper will describe the mechanisms for enforcing environmental laws that apply in Indonesia. This type of research uses juridical-normative.